Comparison of epidural and intra muscular pethidine analgesia in labour : a randomized controlled trial - Ellepola, H.K (My University, 2005)
Objectives of this randomized controlled study to compare effectiveness of epidural analgesis with intramuscular pethidine analgesia in labour with regards to pain relief, duration of labour, incidence of obstetric interventions, malposition, maternal complications and neonatal out come. Study population was two hundred and ninety six uncomplicated primigravidae. Patient were randomly allocated to two groups. In the epidural group following a test dose 0.125 percentage bupivacaine and 2u/ml Fentanyl was administered. Top ups with 0.25 percent bupivacaine were given for break through pain. In the pethidine group intramuscular pethidine was administrated according to body weight. Repeat doses ware gives for break through pain after considering progression labour and time interval of first dose. Using numerical pain scales assessed pain relief. Other parameter assessed was duration of labour, mode of delivery and fetal out come. Patients in the epidural group had more satisfactory pain relief during all stages of labour compared to pethidine (p0.001). Duration of 2nd stage significant prolong in the epidural group compared to the pethidine group